2020
DOI: 10.1080/20473869.2020.1737469
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of professional caregivers on quality of life of persons with profound intellectual and multiple disabilities: a qualitative study

Abstract: Persons with Profound Intellectual and Multiple Disabilities (PIMD) are supported by professional caregivers for a large part of their lives. However, the perspectives of professional caregivers on good or poor Quality of Live (QoL) of persons with PIMD have hardly been explored. To explore the perspective of professional caregivers on QoL of persons with PIMD, we performed a qualitative study, conducting semi-structured interviews with eleven professional caregivers and thematically analysed them. In the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
1
32
0
4
Order By: Relevance
“…Such reconsideration of interpersonal contact between staff and persons with disabilities in determining quality of care, instead of the current focus on quantifiable criteria, was suggested by Reinders (2010) earlier. Such reconsideration would also be in line with Nieuwenhuijse et al (2020) who suggested a relation between the quality of life of persons with profound intellectual disabilities and their interpersonal relationship with staff.…”
Section: Limitationssupporting
confidence: 54%
See 1 more Smart Citation
“…Such reconsideration of interpersonal contact between staff and persons with disabilities in determining quality of care, instead of the current focus on quantifiable criteria, was suggested by Reinders (2010) earlier. Such reconsideration would also be in line with Nieuwenhuijse et al (2020) who suggested a relation between the quality of life of persons with profound intellectual disabilities and their interpersonal relationship with staff.…”
Section: Limitationssupporting
confidence: 54%
“…They mentioned practical circumstances, such as sufficient time and staff. Having to cope with these practical circumstances was also mentioned by staff members in the study of Nieuwenhuijse et al (2020) in relation to quality of life of persons with profound intellectual disabilities, as they described that in some cases they knew how to support the person with profound intellectual disabilities best, but could not provide that care because of challenges regarding financial or human resources. Next to having to cope with practical challenges, in our study, staff also reported they sometimes felt they had to cope with differences in the value given to moments of contact.…”
Section: Discussionmentioning
confidence: 99%
“…However, some parents felt irreplaceable in the life of their child and/or felt they and their child were inseparable (Bowey & McGlaughlin, 2005;Iacono et al, 2016;Stringer et al, 2018). Future research should focus on the situation and estimated QoL of persons with PIMD that actually have outlived their parents, to further explore this relational aspect of QoL for people with PIMD that both parents and medical professionals (Nieuwenhuijse et al, 2019;Nieuwenhuijse et al, 2020) emphasise. This is not only important to better understand the QoL of people with PIMD, but also because this relational view of QoL has consequences for the way parents make medical decisions on behalf of their child, as we have described in our results.…”
Section: Future Fulfilment Of Parental Rolesmentioning
confidence: 99%
“…Taking charge of a person with PIMD is, therefore, a particularly demanding task for all their caregivers (Luijkx et al, 2019). Furthermore, in terms of Quality of Life (Granlund et al, 2013), there is a close relationship between the Quality of Life of the young person with disabilities and his/her family: the lower level of Quality of Life of the young person corresponds to a significant decrease in the Quality of Life of their family (Blacher, 2001;Giaconi, 2015;Nieuwenhuijse, Willems, van Goudoever & Olsman, 2020).…”
Section: The Delicate Life Path Of Families With Members With Pimd In...mentioning
confidence: 99%